Construction of Wife's Permit on Polygamy Practice of Tablig Pilgrim's Mayangan Jogoroto Jombang - Achmad Fageh; Ahmadun Najah (AL-HUKAMA: The Indonesian Journal of Islamic Family Law, 2022)
The focus of this study is the construction of the wife's license to practice polygamy on Tablig Mayangan Jombang Pilgrims. The purpose of the study is to find out the practice of polygamy Of Tablig Mayangan Pilgrims and the model of the wife's license to practice polygamy Tablig Pilgrims Mayangan. This type of field research is qualitative, using the analysis of normative legal and sociological approaches, with inductive reasoning and Data collection techniques using observation, documentation, and interviews. The results showed that polygamous behavior carried out by Tablig pilgrims is based on rational and sharia-laden aspects because polygamous behavior arises due to consideration of the struggle of da'wah as Tablig pilgrims. Polygamy is also considered worship for the husband and wife of Tablig worshippers. Therefore, the practice of polygamy of the husbands and husbands of Tablig pilgrims strictly follows the provisions stipulated in Law No.1 of 1974, article 4 paragraph 2 about committing the cause of polygamous marriage by obtaining the wife's permission. The construction model of the wife's license to practice polygamy Tablig pilgrims is the model of Wira'i, which considers prudence over the property of the third wife as a rich man to avoid disputes over the seizure of Gono - Gini property and so on.